STUDY PENERAPAN PENGELOLAAN SAMPAH DI TPA KUPANG KECAMATAN JABON KABUPATEN SIDOARJO - Putri Nevy Dewi Tara; Bambang Sunarko; Ferry Kriswandana (Poltekkes Kemenkes Surabaya, 2015)
Garbage is resulted from human activities and their existence is unwanted. High population growth can causean increase in garbage volume. This situation calls for right and proper garbage management. Such garbagemanagement can be done in the landfill.The research was carried out in Kupang Landfill at Kecamatan Jabon Kabupaten Sidoarjo. This was adescriptive study, using cross sectional approach. This study illustrated the garbage managementimplementation in Kupang Landfill in Kecamatan Jabon Kabupaten Sidoarjo in 2014. The data were analyseddescriptively based on the tabulated data using fulfillment standard as 50%.The results indicated a score of 65% on garbage management implementation in the Landfill that is inaccordance with the Minister of Public Works Regulation Number 3 Year 2013 regarding The Implementationof Garbage Infrastructure in Household Garbage Handling and Garbage Similar to Household Garbage. Thegarbage management method adopted in Kupang landfill is a controlled landfill. Garbage comes fromresidential areas, markets and manufacturing companies or industries. The daily generation rate of garbage isin the average of 376 m3/ day. The type of the produced garbage is household garbage and similar to those.In terms of the composition it consists of organiC and inorganic garbage. The equipment and tools being usedin garbage management are dump truck, arm roll, pick up, bulldozer, broom, small water pump, big dieselengine, and methane gas suck blower.It is suggested to perform some sorting between garbage from manufacturing companies or industries withpublic garbage. Garbage grouping is based on garbage composition which can be expressed in % of weight or% of volume of each garbage composition, conduct garbage sorting and grouping since garbage leaves itssources, provide sorting facilities, a place for every type of garbage, and provide sorted garbage collectionfacility